PERSONAL HYGIENE DAN PENGGUNAAN ALAT PELINDUNG DIRI TERHADAP GEJALA DERMATITIS PADA PETUGAS PENGANGKUT SAMPA - Samuel Marganda Halomoan Manalu; Imelda Yosepa Nainggolan (JURNAL KESMAS DAN GIZI (JKG), 2022)
Dermatitis is a skin disorder characterized by inflammation and irritation. Symptoms of dermatitis are often found in garbage collectors. This is caused by poor personal hygiene behavior and the lack of use of PPE for each officer when carrying out their work activities. Garbage collectors are workers with direct contact or contact with garbage. This study aims to determine the relationship between the cleanliness of toenails and fingernails, skin hygiene, the use of personal protective equipment, clothing hygiene with symptoms of dermatitis of waste transport officers in Lubuk Pakam District. This study used an analytical survey with a cross sectional design. The population in the study was 50 officers with a sample using the total population. The results showed that there was a significant relationship between the cleanliness of toenails and fingernails (p = 0.003), the use of personal protective equipment (p = 0.001) caused symptoms of dermatitis, for clothing hygiene (p = 0.279), and skin hygiene (p = 1,000) did not. there is a significant relationship with the symptoms of dermatitis.